The role of extracurricular religion in fostering the religious character of students - Wagiyo, Wagiyo; Ahyani, Nur; Destiniar, Destiniar (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
This research seeks to establish and explain the role of extracurricular religious activities in promoting the religious character of students. This research, using a descriptive approach, is a qualitative study. The study objective is to carry out extracurricular religious activities in an attempt to instill the religious beliefs of SMP Negeri 8 Talang Ubi students.The method of collecting data from this analysis is through techniques of observation, interview and recording. A technique that suits the data is used in analyzing this information, namely descriptive data.It can be inferred from the results of the study that the preparation of extracurricular religious activity activities, like majelis taklim, reading and writing the Koran and praying in congregation, aims to build good character in students and can instill a sense of faith and piety in students.